Name unknown - Raffensperger, Christian, author.
1 online resource
Keywords: "Name Unknown offers an example of an eastern European queen as a corrective to the western European focus of medieval queenship studies. This book is of great use to students and scholars interested in the history of women, queenship, and medieval Europe"--